Differences of effect between running and roller ski training - Cetin, E.; Günay, M.; Yarim, I. (4th International Congress on Science and Skiing, 2007)
SUMMARY: The purpose of this investigation was to determine the effects of roller ski and running training programs on maxVO2 and other physiological parameters of cross- country skiers. With this aim, 24 cross-country skiers at national level, voluntarily participated in the study. The mean age of the subjects was14.42 ±1.21 years. The subjects were trained four times in a week with the duration of 8 weeks training period. Subjects in the study divided into three groups as roller ski (n=8), running(n=8) and mixed (n=8) training groups. Training intensity were applied according to 70-85 % of target heart rate for each subjects. Roller ski and running groups were trained 4 times in a week in contrast to mixed group. Mixed group was participated two times per week in running program and two times in ski training program. Training intensity, was determined before the training programs.